Sollicitudo Rei Socialis Dan Migrasi : Mencari Solusi Kemanusiaan Di Tengah Krisis Global - Maria Erdila Dete; Teresia Noiman Derung (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
In the 21st century, the increasingly complex phenomenon of global migration has become a major challenge for humanity, as migration issues are often linked to conflict, poverty, social injustice, and climate change. In this context, the encyclical Sollicitudo Rei Socialis written by Pope John Paul II provides a relevant framework for understanding and responding to the migration crisis. This document emphasizes that in order to build a more just and humane society, human dignity, social justice, and global solidarity are essential. The purpose of this study is to instill the extent to which the principles contained in Sollicitudo Rei Socialis can serve as a basis for developing comprehensive solutions to the migration problem. This study will find the difficulties and opportunities in applying these principles in migration policies by investigating the literature and analyzing cases. This study is expected to help develop more humane and sustainable migration policies. In addition, this study is expected to inspire the wider community to participate in solidarity efforts towards migrants.